Living Literacies: Literacy for Social Change - Rowsell, Jennifer; Rowsell, Jennifer (Cambridge, Massachusetts : The MIT Press, 2020)
"Pahl and Rowsell combines newer orientations in literacy studies - co-production, new materialism, post-humanism, digital and maker epistemologies - to describe a living, enacted model of literacy"
Keywords: Literacy -- Social aspects -- Research; Critical pedagogy